2014
DOI: 10.1016/j.jml.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The difference between “giving a rose” and “giving a kiss”: Sustained neural activity to the light verb construction

Abstract: We used event-related potentials (ERPs) to investigate the neurocognitive mechanisms associated with processing light verb constructions such as “give a kiss”. These constructions consist of a semantically underspecified light verb (“give”) and an event nominal that contributes most of the meaning and also activates an argument structure of its own (“kiss”). This creates a mismatch between the syntactic constituents and the semantic roles of a sentence. Native speakers read German verb-final sentences that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
32
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 51 publications
9
32
0
Order By: Relevance
“…In this sense, the relatively delayed late anterior negativity effect in this study may be a more direct reflection of narrative or event structural surprisal/prediction error. This interpretation would be consistent with recent reports of late onset anterior negativities to words that match (versus mismatch) one of two possible event structures that are anticipated in certain sentence and discourse contexts (Baggio, van Lambalgen, & Hagoort, 2008; Paczynski, Jackendoff, & Kuperberg, 2014; Wittenberg, Paczynski, Wiese, Jackendoff, & Kuperberg, 2014; Wlotko & Federmeier, 2012). …”
Section: Discussionsupporting
confidence: 91%
“…In this sense, the relatively delayed late anterior negativity effect in this study may be a more direct reflection of narrative or event structural surprisal/prediction error. This interpretation would be consistent with recent reports of late onset anterior negativities to words that match (versus mismatch) one of two possible event structures that are anticipated in certain sentence and discourse contexts (Baggio, van Lambalgen, & Hagoort, 2008; Paczynski, Jackendoff, & Kuperberg, 2014; Wittenberg, Paczynski, Wiese, Jackendoff, & Kuperberg, 2014; Wlotko & Federmeier, 2012). …”
Section: Discussionsupporting
confidence: 91%
“…Both the different-syntax and different-semantics accounts, however, would strain to explain such a mechanism: Light verb constructions are extremely frequent, unlike the garden-path sentences used in the shallow parsing literature, and adults have ample practice in using and comprehending these structures (Piñango et al, 2006; Wittenberg et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…being interrupted by coffee spilling on the paper). And, most recently our group (Wittenberg et al, 2014) observed a late, sustained widely-distributed, but frontally focused, negativity from 500ms following verbs in light verb constructions (e.g. “Julius gave Anne a kiss”)—another type of complex event structure in which the subject of the sentence acts both as the Agent of the verb and of the direct object (so-called argument sharing, cf.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the non-completion of the letter-writing event is again inferred, but not explicitly stated. And, third, we (Wittenberg, Paczynski, Wiese, Jackendoff, & Kuperberg, 2014) recently observed a sustained negativity effect starting at 500ms after the onset of verbs in light verb constructions (e.g. original German: “Als die Stewardess eine Ansage machte …”; English translation: “When the stewardess made an announcement…”).…”
Section: Introductionmentioning
confidence: 92%